The Role of Vasoactive Intestinal Peptide and Mast Cells in the Regulatory Effect of Lactobacillus casei ATCC 393 on Intestinal Mucosal Immune Barrier - Song, Xiaofan; Pi, Shanyao; Gao, Yueming; Zhou, Fengxia; Yan, Shuqi; Chen, Yue; Qiao, Lei; Dou, Xina; Shao, Dongyan; Xu, Chunlan (Frontiers in Immunology, 2021)
Vasoactive intestinal peptide (VIP) plays an important role in the neuro-endocrine-immune system. Mast cells (MCs) are important immune effector cells. This study was conducted to investigate the protective effect of L. casei ATCC 393 on Enterotoxigenic Escherichia coli (ETEC) K88-induced intestinal mucosal immune barrier injury and its association with VIP/MC signaling by in vitro experiments in cultures of porcine mucosal mast cells (PMMCs) and in vivo experiments using VIP receptor antagonist (aVIP) drug. The results showed that compared with the ETEC K88 and lipopolysaccharides (LPS)-induced model groups, VIP pretreatment significantly inhibited the activation of MCs and the release of β-hexosaminidase (β-hex), histamine and tryptase. Pretreatment with aVIP abolished the protective effect of L. casei ATCC 393 on ETEC K88-induced intestinal mucosal immune barrier dysfunction in C57BL/6 mice. Also, with the blocking of VIP signal transduction, the ETEC K88 infection increased serum inflammatory cytokines, and the numbers of degranulated MCs in ileum, which were decreased by administration of L. casei ATCC 393. In addition, VIP mediated the regulatory effect of L. casei ATCC 393 on intestinal microbiota in mice. These findings suggested that VIP may mediate the protective effect of L.casei ATCC 393 on intestinal mucosal immune barrier dysfunction via MCs.